Symbolism 2020 an international annual of critical aesthetics - Ahrens, Rüdiger 1939-; Kläger, Florian; Stierstorfer, Klaus 1961-; Tronicke, Marlena 1987- (De Gruyter, 2020)
This special anniversary volume of Symbolism explores the nexus between symbolic signification and the future from an interdisciplinary perspective. How, contributors ask, has the future been variously rendered in symbolic terms? How do symbols and symbolic reference shape our ideas of the future? To what extent are symbols constitutive of futures, and to what extent do they restrain communication about what is possible and the imagination of fundamental change? Moreover, how have symbolic practices shaped not only artistic representations of the future, but also scientific attempts at forecasting and modelling it? What, then, is the relevance of symbolism for negotiations of the future in cultural and academic production? In essays ranging from literary and film studies to the philosophy of art and ecological modelling, the volume seeks to lay groundwork in theorizing and historicising 'symbols of the future' as much as 'the future of symbolism'
Special focus: symbols of the future/the future of symbolism
Keywords: Symbol; futures studies; literary form; symbolism; Zukunft; Ästhetik; Symbolismus; Aufsatzsammlung